Reconstruction of vegetation dynamics in “Linje” peat-bog (N Poland) using remote sensing method - Ejankowski, Wojciech; Kunz, Mieczysław (Biodiversity: Research and Conservation, 2006)
The study reports vegetation changes in the "Linje" nature reserve in the Chełmińskie Lakeland (N Poland), a locality of a glacial relict dwarf birch Betula nana L. Former condition of the peat-bog vegetation was determined by the use of the remote sensing method, based on a set of aerial photographs from 1951-1996. In the second half of 20th century, in the area occupied by B. nana, a Pinus sylvestris forest extincted. In 1978-1996, the area of scrubs and forests dominated by Betula pubescens increased by ca. 100%, and open bog communities decreased of 22%. Expansion of B. pubescens negatively influenced the abundance of B. nana, whereas the extinction of the pine stand and the development of Ledum palustre dominated communities instead, probably improved conditions for existence of the dwarf birch.